Aspek Hukum Pembentukan Qanun No. 3/2013 tentang Bendera dan Lambang Aceh - Kurniawan Kurniawan (Kanun Jurnal Ilmu Hukum, 2014)
This article aims is to explain the basic authority of the enactment of Qanun (local law) Aceh No. 3, 2013 regarding the Flag and Symbol of Aceh. Furthermore, it examines whether the law infringes higher laws and public interest. In addition, it explores the validity of the law and its legal mechanism which is available regarding the cancellation of the law. This   is  normatif legal research. The data is obtained through library research. The approach research used is statute approach. The findings show that, the law infringes Government Regulation No. 77, 2007 regarding the Symbof of Region and public interest. Nevertheless, the existence of the law is legally valid because the Government has exceeded the time period of 60 days since it received the law, and has not issued the President Regulation regarding the cancellation of it. It means that if the Government has not issued it, it is legally that the law is valid as mandated in Article 145 paragraph, sub article (7) of the Act No. 32,  2004 regarding on the Local Government . The Legal Aspect of The Enacment Qanun Number 3, 2013 Regarding The Flag and Emblem of Aceh